HAMBATAN KOMUNIKASI ANTARBUDAYA DI KALANGAN PELAJAR ASLI PAPUA DENGAN SISWA PENDATANG DI KOTA JAYAPURA - Anwar, Rostini (Jurnal Common, 2018)
Penelitian ini dilatarbelakangi oleh hambatan komunikasi antarbudaya yang terjadi di kalangan Pelajar Asli Papua (OAP) dengan Pelajar Pendatang. Tujuan penelitian ini adalah untuk mendeskripsikan dan menganalisis hambatan komunikasi antarbudaya siswa asal Papua khususnya di SMA YPPK Teruna Bakti Jayapura. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Dalam penelitian ini, penulis menggunakan teknik purposive sampling (bertujuan) untuk pemilihan subjek, dengan jumlah informan sebanyak 10 (sepuluh) orang siswa – siswi. Sumber data yang digunakan adalah sumber data primer dan data sekunder yang berkaitan dengan situasi dan kondisi empiris. Wawancara dan dokumentasi guna memperoleh data primer mengenai Hambatan Komunikasi Antarbudaya siswa asli papua dengan siswa pendatang di SMA YPPK Teruna Bakti Jayapura. Hasil penelitian menunjukkan bahwa hambatan komunikasi antarbudaya masih sering terjadi karena masing – masing suku masih mengalami kesulitan dalam memahami setiap perbedaan budaya. Adapun yang menjadi faktor penghambat komunikasi antarbudaya adalah mengenai perbedaan bahasa, kesalahpahaman nonverbal (seperti gestur tubuh, suara dan sebagainya) serta dalam persepsi mereka dalam menilai masing – masing kedua suku tersebut. --------------------------------------------------------------------------------- This research is motivated by intercultural communication barrier that happened among students of native Papuan with students Papuan immigrants in Jayapura. The purpose of this research is to describe and analyze the barriers of intercultural communication of students native Papuan in SMA YPPK Teruna Bakti Jayapura. The method used in this research is descriptive qualitative method. In this research, the writer uses purposive sampling technique for the selection of subject, with the informants as much 10 students. The data source used is primary data source and secondary data relating to empirical situation and condition. Interviews and documentation to obtain primary data on intercultural communication barriers of Papuan students and immigrans students of Jayapura at SMA YPPK Teruna Bakti. The results showed that intercultural communication barriers are still frequent because each tribe still has difficulty in understanding every culture difference. The inhibiting factors of intercultural communication are language differences, nonverbal misconceptions (such as body gestures, voices and so on) and in their perceptions of judging each of the two tribes.d by intercultural communication barrier that happened among students of native Papuan with students Papuan immigrants in Jayapura. The purpose of this research is to describe and analyze the barriers of intercultural communication of students native Papuan in SMA YPPK Teruna Bakti Jayapura. The method used in this research is descriptive qualitative method. In this research, the writer uses purposive sampling technique for the selection of subject, with the informants as much 10 students. The data source used is primary data source and secondary data relating to empirical situation and condition. Interviews and documentation to obtain primary data on intercultural communication barriers of Papuan students and immigrans students of Jayapura at SMA YPPK Teruna Bakti. The results showed that intercultural communication barriers are still frequent because each tribe still has difficulty in understanding every culture difference. The inhibiting factors of intercultural communication are language differences, nonverbal misconceptions (such as body gestures, voices and so on) and in their perceptions of judging each of the two tribes.